The prose poem in the Arabic rhetorical perspective - Hussein, Legaa Adel (Al-Adab Journal, 2022)
The prose poem is a literary term that has recently emerged and competed, and it was created in its season, and it was possible, to be independent from them. The on analysis and detail to probe the depths of his rhetoric. This art has found supporters, in addition to having met with opponents a fierce war that took it out of the Arab arts, but it is a well-known Arab art that has roots extending to poetry and literature, it combined their characteristics, until it was said that it was present in the shrine, and the writings of the ancients, so it was necessary the search for this art and its origins, and an explanation of the original and the objectionable attached to it. The research was divided into an introduction after the introduction: the first topic: the concept of the prose poem and its origin, the second topic: the characteristics of the prose poem, the third topic: rhetorical arts in examples of prose poems.